Hacktivism - Hanna Gawel (Internet Policy Review, 2024)
Hacktivism represents a dynamic intersection of technology and activism, where individuals or groups leverage digital tools to advance social or political causes. This text explores the multifaceted nature of hacktivism, encompassing a spectrum of activities from online protests and information dissemination to more disruptive forms of digital direct action.
Keywords: 300; Hacktivism; Hacking; Hacker; Political activism